Effect of Plant Growth Regulators on Tiller Dynamics and Yield of Sugarcane (Saccharum officinarum L.) - Praharaj, Subhashisa; Singh, Dheer; Guru, S. K.; Meena, Bolta Ram (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during spring 2015–16 at Pantnagar, Uttarakhand with the objective to study the effect of ethephon and gibberellic acid on tiler dynamics, millble cane production and yield of sugarcane. Ten treatments i.e. conventional planting (T1), overnight soaking of setts in water (T2), overnight soaking of setts in 50 ppm ethephon (T3), overnight soaking of setts in 100 ppm ethephon (T4), T1+foliar application of GA3 @ 35 ppm at 90, 120 and 150 DAP (T5), T2+foliar application of GA3 @ 35 ppm at 90, 120 and 150 DAP (T6), T3+foliar application of GA3 @ 35 ppm at 90, 120 and 150 DAP (T7), T4+foliar application of GA3 @ 35 ppm at 90, 120 and 150 DAP (T8), soaking of setts for six hours in 50 ppm ethephon (T9) and six hour soaking of setts in 100 ppm ethephon (T10) were laid down in a randomized block design with 3 replication. Soil of the experiment plot was silty clay loam having high organic carbon (1.04%), high available phosphorus (32.5 kg ha-1), medium in available potassium (256.2 kg ha-1) and low in available nitrogen (233.4 kg ha-1). The soil was neutral in pH (7.2). The treatment in which setts were planted after overnight soaking with 100 ppm ethephon followed by foliar application of gibberellic acid @ 35 ppm at 90, 120 and 150 DAP was found to improve tiller production, number of millable canes and yield of the crop.